2018
DOI: 10.18051/univmed.2018.v37.57-64
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous IR Bagendit rice leaf extract decreases reticulocyte count in lead-exposed rats

Abstract: BACKGROUNDLead acetate may inhibit the enzyme aminolevulinate dehydratase (ALAD) resulting in decreased heme synthesis (and consequently in anemia) but in increased number of reticulocyte cells. IR Bagendit paddy leaf water extract has a high metallothionein protein content which acts to bind to lead. The study objective was to determine whether aqueous IR Bagendit rice leaf extract dosage variations prior to lead exposure decreases reticulocyte count in lead-exposed rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…20 Protein metallothionein in (Oryza sativa L) IR-Bagendit rice leaves has a sulfhydryl group and can bind PB acetate; thus, this protein metallothionein is stable for the detoxification process. 21,22 This study has found that the provision of IR-Bagendit rice (Oryza sativa L) leaf infusion of 0.2 ml/day, 0.4 ml/day, and 0.8 ml/day can successively decrease necrosis cell damage up to 75% in P1, 90% in P2, and 100% in P3. These numbers show that the intervention groups have significantly different improvements from the positive control group.…”
Section: Necrosis Normal Cellsmentioning
confidence: 96%
See 1 more Smart Citation
“…20 Protein metallothionein in (Oryza sativa L) IR-Bagendit rice leaves has a sulfhydryl group and can bind PB acetate; thus, this protein metallothionein is stable for the detoxification process. 21,22 This study has found that the provision of IR-Bagendit rice (Oryza sativa L) leaf infusion of 0.2 ml/day, 0.4 ml/day, and 0.8 ml/day can successively decrease necrosis cell damage up to 75% in P1, 90% in P2, and 100% in P3. These numbers show that the intervention groups have significantly different improvements from the positive control group.…”
Section: Necrosis Normal Cellsmentioning
confidence: 96%
“…This protein is rich in sulfhydryl groups that could covalently bind heavy metals (Pb). 12,13 The content of metallothionein proteins in IR Bagendit rice leaves from various locations in Northern Java has been investigated, and the investigation has revealed that R Bagendit rice from Blora has the highest content. 14 The metallothionein gene is located on chromosome 3 of IR Bagendit rice leaves (Oryza Sativa) and functions as stress-inducible proteins in drought conditions as well as soil and water-containing metals.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Anemia terjadi karena sintesis heme tidak terbentuk. 10,11 Pada proses sintesis heme, timbal menghambat enzim δ ALAD (amino levulinic acid dehydratase) sehinga mengakibatkan terhentinya δ ALA (δ amino levulinic acid) menjadi porphobilinogen (PBG). 12 Hal ini dapat mengakibatkan peningkatan kadar δ ALA dalam darah dan urin.…”
Section: Pendahuluanunclassified
“…IR Bagendit rice leaves-infused water is rich in the metallothionein protein (Santosa et al, 2018;Santosa et al, 2020) and has many sulfhydryl groups that function in the HG detoxication mechanism. A large number of sulfhydryl groups in the metallothionein protein affects the protein's ability to bind Hg.…”
Section: Introductionmentioning
confidence: 99%